Does the Stock Market Affect the Real Economy? An Empirical Analysis Based on China’s Stock Market Liquidity - Chao Wang; Jia Hao (Discrete Dynamics in Nature and Society)
This article investigates the causal effect between the stock market and the real economy. Based on the data of China’s A-share market from 1998 to 2017, this article uses the fixed-effect model and other methods to find the causal effect from the perspective of the impact of illiquidity at the individual stock level on enterprise investment decision-making. Empirical results show that stock illiquidity significantly decreases enterprise investment. Information asymmetry is one of the important channels between the stock market and the real economy. The financial constraints and agency conflicts caused by information asymmetry significantly affect the causal effect. Macroeconomic policies to alleviate market information asymmetry can effectively act on the real economy through the stock market. From the microperspective of studying the causal effect, this study controls the time effect and individual effect and further explores the influence mechanism between the stock market and the real economy. Research shows that macroeconomic policies can effectively affect the real economy through the stock market and provides decision-making references for future macropolicy formulation.